Clinical and cost-effectiveness of the digital intervention, MyWay Diabetes, in people with type 2 diabetes living in Greater Manchester during the COVID-19 pandemic - Rathi Ravindrarajah; Matthew Gittins; Luke Paterson; Gabriel Rogers; George Tilson; Deborah J. Wake; Doogie Brodie; Scott G. Cunningham; Naresh Kanumilli; Ewan Jones; Peter Elton; Nicola Milne; et al. (PLoS ONE, 2026)
Aims We aimed to assess a) whether using the digital intervention, MyWay Diabetes (MWD), during the COVID-19 pandemic in Greater Manchester was associated with improvements in glycaemia and cardiovascular risk factors; and b) the cost-effectiveness of MWD. Methods From 01 st July 2019–30 th April 2022, we assessed risk factor changes in MWD users (n = 507) with T2D, adjusting for changes in a matched control group of non-users (n = 10,135). Economic evaluation was conducted using United Kingdom Prospective Diabetes Study Outcomes Model version 2.1 simulating 1,000 patients over 40-years based on observed risk factor changes. Results Over 2-years follow-up, MWD use was associated with a clinically significant reductions in HbA1c of 3.1 (95%CI: 1.5 to 4.6) mmol/mol and decreases in systolic blood pressure (1.4 (0.2 to 2.6) mmHg) and cholesterol (0.1 (0.02 to 0.2) mmol/L) when compared to non-users. Including medication costs, MWD generated more health (0·015 QALYs) and lower costs (−£67 per person) compared to usual care. Excluding medication costs, MWD generated QALYs at a cost of £389 each, below the NICE threshold of £20,000–30,000/QALY. Interpretation At population level, the risk factor changes associated with MWD are likely to reduce long-term diabetes-related complications risks and the intervention appears cost-effective.